Strawberry Germplasm Influences Fruit Physicochemical Composition More than Harvest Date or Location - Brianna Haynes; Gina Fernandez; Guoying Ma; Hsuan Chen; Penelope Perkins-Veazie (Horticulturae, 2025)
Strawberries (Fragaria × ananassa) are highly valued for their colorful fruit and flavorful taste. Anthocyanins provide much of the red fruit color, and the flavor is highly affected by soluble sugars and non-volatile organic acids. These fruit composition parameters impact consumer decisions. In this study, strawberry fruits from 17 commercial cultivars and advanced selections were collected weekly from replicated trials at three locations in North Carolina. The relative effects of the location and germplasm on fruit composition were determined, including the soluble solid concentration (SSC), titratable acidity (Tacid), and total anthocyanin content (TAC). The breeding criteria of at least 8.0% SSC and 0.80% Tacid were met by eight and six genotypes, respectively and five of these met both criteria. The fruit TAC ranged from 24.0 to 45.7 mg pelargonidin-3-O-glucoside (P3G) equivalents/100 g FWT. P3G was the dominant pigment in all genotypes, followed by pelargonidin-3-O-rutinoside (P3R). As harvest dates advanced, pH, TAC, P3G, P3R, and pelargonidin-3-O-(6″-malonylglucoside) (P3MG) generally decreased, while Tacid, SSC, and cyanidin-3-O-glucoside (C3G) increased. Composition of field-grown strawberries in this mid-Atlantic location were more influenced by the genotype and harvest date than by the growing location.